Selectively expressed RNA molecules as a versatile tool for functionalized cell targeting - Frederik Rastfeld; Marco Hoffmann; Sylvie Krüger; Patrick Bohn; Anne-Sophie Gribling-Burrer; Laura Wagner; Nils Hersch; Carina Stegmayr; Lukas Lövenich; Sven Gerlach; Daniel Köninger; Christina Hoffmann; et al. (Nature Communications)
Abstract Targeting of diseased cells is one of the most urgently needed prerequisites for a next generation of potent pharmaceuticals. Different approaches pursued fail mainly due to a lack of specific surface markers. Developing an RNA-based methodology, we can now ensure precise cell targeting combined with selective expression of effector proteins for therapy, diagnostics or cell steering. The specific combination of the molecular properties of antisense technology and mRNA therapy with functional RNA secondary structures allowed us to develop selectively expressed RNA molecules for medical applications. These seRNAs remain inactive in non-target cells and induce translation by partial degradation only in preselected cell types of interest. Cell specificity and type of functionalization are easily adaptable based on a modular system. In proof-of-concept studies we use seRNAs as platform technology for highly selective cell targeting. We effectively treat breast tumor cell clusters in mixed cell systems and shrink early U87 glioblastoma cell clusters in the brain of male mice without detectable side effects. Our data open up potential avenues for various therapeutic applications.